Educación basada en el cerebro. - Franco Corso, Silvia Juliana (MedUNAB)
Introduction: Brain functioning-based learning seeks to maximize the ability of the brain to learn - memory, attention, understanding - based on the neuroscientific findings. Development: In this article we summarize some of the findings on the brain processes and how these can be applied to the classroom or, in general, the learning process. Conclusion: Dividing the class in short time blocks, using visual stimulations or eliciting emotions might be useful ways to maximize student's classroom performance. In addition, eating properly, exercising and making reading or memory exercises might be a key to brain stimulation and preventing cognitive impairment in older ages.